Improving Integrated Practice through Building Information Modeling-Integrated Project Delivery (BIM-IPD) for Malaysian Industrialised Building System (IBS) Construction Projects - Mohd Nasrun, Mohd Nawi; Ahmad Tarmizi, Haron; Zuhairi, Abd Hamid; Kamarul Anuar, Mohamad Kamar; Yusnizam, Baharuddin (Construction Research Institute of Malaysia, 2014)
Current studies shows that most of the Industrialised Building System (IBS) project procurement or delivery methods in Malaysia are still based on the traditional approach. This traditional construction process has been widely criticized for its fragmented approach to project delivery and its failure to form effective teams. Due to that problem, a number of issues have recently arisen in current construction methods, such as reworks, time delay, rising costs, lack of communication and coordination, and wastages. This paper through literature review aims to explore this fragmentation issue thus effects to the Malaysian IBS construction projects especially during the design and construction stages. Suggestion on how an integrated approach such as Building Information Modelling (BIM) and Integrated Project Delivery (IPD) can contribute for design and construction process in order to minimise the fragmentation issue will be concluded.